Pengetahuan Dan Kekuasaan Tentang Wacana Medis Dalam “Skin Wiki” oleh Klinik Kecantikan Erha - Arif Zuhdi Winarto (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2022)
Michel Foucault sparked the thought of the reciprocal relationship between Power and Knowledge (Foucault 1982b). The administration of power will continuously create knowledge entities, and vice versa the implementation of knowledge will cause the effect of power. Discourse of truth is formed and produced through a process and mechanisms of power. ERHA beauty clinic as one of the aesthetic franchise clinics spread across several regions in Indonesia that focuses on dealing with body appearance issues from hair to nails. This clinic has a different marketing strategy from its competitors, namely by producing medical discourse into a glossary catalog called SKIN WIKI. As Foucault thought about the birth of the clinic, in the Skin Wiki things related to the body are given a specific label in medical discourse so that what is unusual is considered a deviant and must be taken seriously in a personal, precise and specific way. It also implies that if the deviation is not handled professionally it will make the condition of that particular person even worse. This paper tries to explain that medical discourse in Skin Wiki by Erha clinic is an inseparable part of the process and mechanism of power to form a beauty image that can attract patients as the target market to come and seek treatment at the Erha beauty clinic. From the knowledge released by the Erha Clinic, Erha's beautiful construction is a personal beauty, free from any discourse of irregularities or discourses of abnormality.